2003
DOI: 10.1603/0022-0493-96.2.352
|View full text |Cite
|
Sign up to set email alerts
|

Plant Damage and Yield Response to the Russian Wheat Aphid (Homoptera: Aphididae) on Susceptible and Resistant Winter Wheats in Colorado

Abstract: Plant damage and yield response to the Russian wheat aphid, Diuraphis noxia (Mordvilko), were evaluated on a susceptible (TAM 107) and a resistant (RWA E1) winter wheat, Triticum aestivum L., in three Colorado locations in the 1993 and 1994 crop years. Russian wheat aphid was more abundant on TAM 107 than on RWA E1. Russian wheat aphid days per tiller were greater at the higher infestation levels. Yield losses as a result of Russian wheat aphid infestation occurred most of the time with TAM 107 but rarely with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Management of D. noxia has largely relied on resistant wheat cultivars (Smith 1999, Webster andKenkel 1999). Wheat cultivars containing D. noxia-resistant genes, which have different levels of antibiosis, tolerance, or both (Randolph et al 2005a), have been shown to harbor fewer D. noxia populations and have higher yields compared with their susceptible wheat counterparts (Randolph et al 2003(Randolph et al , 2005b. Resistant plants also have demonstrated compatibility with other management tactics by exhibiting an absence of leaf rolling when infested with D. noxia, which would expose the aphids to chemical and biological management (Hawley et al 2003).…”
mentioning
confidence: 99%
“…Management of D. noxia has largely relied on resistant wheat cultivars (Smith 1999, Webster andKenkel 1999). Wheat cultivars containing D. noxia-resistant genes, which have different levels of antibiosis, tolerance, or both (Randolph et al 2005a), have been shown to harbor fewer D. noxia populations and have higher yields compared with their susceptible wheat counterparts (Randolph et al 2003(Randolph et al , 2005b. Resistant plants also have demonstrated compatibility with other management tactics by exhibiting an absence of leaf rolling when infested with D. noxia, which would expose the aphids to chemical and biological management (Hawley et al 2003).…”
mentioning
confidence: 99%
“…Tolerance has been reported for Tugela-Dn2 (Wang et al 2004), Dn4 resistance in PI372129 (Meyer & Peairs 1989) and 'Halt' (Hawley et al 2003). Antibiosis was reported in CO 940626 carrying the Dn4 and Dn6 genes (Al-Ayedh 2000), 'Ankor', 'Stanton' (Randolph et al 2006) and 'Halt' (Hawley et al 2003, Randolph et al 2006, mainly expressed as lower aphid fecundity, while negative affects on developmental biology have been reported in other backgrounds (e.g., Tugela-Dn1, Tugela-Dn2 and Tugela-Dn5 ) (Wang et al 2004). The Dn7 gene confers antixenosis (Anderson et al 2003) as well as antibiosis (Peng & Lapitan, unpublished).…”
Section: Candidate R-genes For Rwa Resistancementioning
confidence: 99%
“…A few previous studies have assessed the development of aphid populations in field trials on wheat germplasm previously evaluated under controlled conditions, e.g. Randolph et al (2003) for Diuraphis noxia (Mordvilko) and Migui and Lamb (2004) for S. avenae.…”
Section: Introductionmentioning
confidence: 99%